Human Capital Development, Infrastructural Development And Industrial Sector Productivity In Nigeria - Enilolobo, Oluwafemi S.; Sodeinde, Olamide (Archives of Business Research, 2019)
This study examines relationship between human capital development, infrastructural development and industrial sector in Nigeria for the period 1991 through 2014. The objective of the study is to identify some critical economic and social factors that influence industrial sector productivity in Nigeria. To ascertain the relationship between our variables of studies, secondary source of data was employed and extracted from World Development Indicators. Using an Ordinary Least square (OLS) estimation technique, the study established that human capital development has positive and significant effect on industrial sector productivity while infrastructural development has positive but insignificant effect on industrial sector productivity in Nigeria. Thus, the study recommends effective negotiation of debt relief from Paris club and other foreign debt to enable the government have excess funds to invest on pro-poor intervention project, transparency in governance and implementation of fiscal budget with post evaluation.